Stances of (in)visibility of the female Negro body: focusing on portinari’s pictorial aesthetics - doi: 10.4025/actascilangcult.v32i2.11653 - Tasso, Ismara Eliane Vidal de Souza; Campos, Jefferson Gustavo dos Santos (Acta Scientiarum. Language and Culture, 2010)
Current analysis investigates the manner identity constitution and black female’s visual representation in Portinari’s iconography is shown within the theoretical presuppositions of the French Discourse Analysis in alignment with the theoretical bases of Peirce’s Semiotics, the History of the Body and Cultural Studies. The social and the political factors are understood through an interpretative stance, within the paradoxical state of intangible significant materiality. The descriptive, interpretative, archeological and genealogical movement showed that the half-naked body is presented as erotic, perceived as exotic and treated as profane. The movement also showed that sensuality is signified and re-signified by the marginal since it works with discursive memory which conceives the exotic as an order opposed to existence, namely the profane order, and the place in which the subjects of difference encounter one another